2007
DOI: 10.1007/s10661-007-9704-4
|View full text |Cite
|
Sign up to set email alerts
|

Current status and perspectives of accelerated carbonation processes on municipal waste combustion residues

Abstract: The increasing volumes of municipal solid waste produced worldwide are encouraging the development of processes to reduce the environmental impact of this waste stream. Combustion technology can facilitate volume reduction of up to 90%, with the inorganic contaminants being captured in furnace bottom ash, and fly ash/APC residues. The disposal or reuse of these residues is however governed by the potential release of constituent contaminants into the environment. Accelerated carbonation has been shown to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 54 publications
(166 reference statements)
0
98
0
3
Order By: Relevance
“…Nature's carbon cycle sequesters CO 2 as mineral carbonates by precipitation from the ocean in a geological timescale (Gerdemann et al, 2007). However, the kinetics of natural carbonation is extremely slow due to the relatively low CO 2 concentration, about 0.03-0.06% (Lackner, 2002;Costa et al, 2007). According to an investigation by Haug et al (2010), the weathering rate of olivine is estimated to be 10 −8.5 mol/(m 2 s) using the average ground temperature in Norway of 6°C and a pH of 5.6, which corresponds to the acidity of rainwater.…”
Section: Natural Carbonationmentioning
confidence: 99%
See 3 more Smart Citations
“…Nature's carbon cycle sequesters CO 2 as mineral carbonates by precipitation from the ocean in a geological timescale (Gerdemann et al, 2007). However, the kinetics of natural carbonation is extremely slow due to the relatively low CO 2 concentration, about 0.03-0.06% (Lackner, 2002;Costa et al, 2007). According to an investigation by Haug et al (2010), the weathering rate of olivine is estimated to be 10 −8.5 mol/(m 2 s) using the average ground temperature in Norway of 6°C and a pH of 5.6, which corresponds to the acidity of rainwater.…”
Section: Natural Carbonationmentioning
confidence: 99%
“…Currently, accelerated carbonation has been primarily investigated through the direct aqueous route (Huijgen and Comans, 2006a;Costa, 2009;Uibu et al, 2009;Chang et al, 2011a). Carbonation can result in lowering of pH, affecting the solubility, and leaching of metals which are mobilized at high pH and fixed at low pH (Costa et al, 2007).…”
Section: Accelerated Carbonationmentioning
confidence: 99%
See 2 more Smart Citations
“…Various sources of alkalinity have been suggested for CO 2 sequestration purposes. For example, alkaline solid residues from different industries such as steel slag (Huijgen & Comans, 2005;Kelly et al, 2011), cement kiln dust (Huntzinger et al, 2009), and fly ashes (Back et al, 2008;Costa et al, 2007), have been identified as alkalinity sources. The quantity and distribution of these alkaline solid wastes is however limited on a global scale (Huijgen & Comans, 2005).…”
Section: Alkalinity Source For Conversion Of Co 2 To Carbonate Ionsmentioning
confidence: 99%